O traço e a pena: a campanha abolicionista de Ângelo Agostini na Revista Illustrada (1884-1888) - Pereira, Washington Kuklinski (2010)
The propose of this research is to study the historical process that resulted in the end of Brazilian slave work force, from the analysis of the caricatures produced by Ângelo Agostini on Revista Ilustrada (Ilustrated Magazine), from 1884 to 1888. The political caricatures that allow people to understand the process which resulted in the elaboration, approval and applicability of the Lei do Sexagenário (Sexagenarian Law) is analyzed. Ângelo Agostini made the abolitionist campaign from Ceará public, he also noticed errors on the law, he used to speak ironically about politicians who expected to be benefited by the slaves proprietors and ridiculate the minister Saraiva, considered by artists as the defender of the attempt to postpone the abolition of the slavery. The relation between the Catholic Church and the Brazilian State about the slavery is analyzed; and how Ângelo Agostini, with the caricatures, used to denounce the torture applied to the slaves by their proprietors and by the police, being ignorated by Brazilian Bishops silence The change of the Imperial Family position about the servile element, like the requirement of the elaboration, approval of the Áurea Law by the Senate, were mentioned by Ângelo Agostini in his caricatures, that magnified the Princess Isabel image as the biggest responsible for the abolition of the slavery in Brazil, admired by the whole Brazilian population, mainly by the free slaves